The financial professional's guide to healthcare reform - Dietrich, Mark O. (Wiley finance series., 2012)
"A comprehensive reference guide interpreting and applying healthcare reform law for consultants, appraisers, accountants, and attorneysThe Financial Consultants'Guide to Healthcare Reform provides an historical backdrop on how the healthcare system got to its present state including the Massachusetts Reform and Medicare Advantage along with an explanation of the principal types of health insurance in the United States and how "insurance" actually works. A review and explanation of each of the reform provisions follows, including an analysis of what the implications are for providers, consumers and business and what responses each of these communities might have to the Reform. Using the authors' insights and firsthand experiences in U.S. healthcare finance, this book explains the new healthcare law for individuals and businesses alike, what to expect from it and what actions they need to take to comply. Interprets and applies the health care reform law Provides examples of what the impact of the law might look like Extensive use of sidebars to provide in-depth analysis or background on particular topics of import, where the reader may need more detail to understand the context of Reform's changes. Written for consultants, appraisers, accountants, and attorneys Written by major figures in the world of healthcare valuation and consulting The Financial Consultants' Guide to Healthcare Reform provides a complete handbook to healthcare reform for financial consultants, both for understanding this important legislation as well as for planning responses to it"--